Residual pulmonary embolism as a predictor for recurrence after a first unprovoked episode: Results from the REVERSE cohort study. Issue 162 (February 2018) - Wan, Tony; Rodger, Marc; Zeng, Wanzhen; Robin, Philippe; Righini, Marc; Kovacs, Michael J.; Tan, Melanie; Carrier, Marc; Kahn, Susan R.; Wells, Philip S.; Anderson, David R.; Chagnon, Isabelle; et al.
Abstract: Background: The optimal duration of oral anticoagulant therapy after a first, unprovoked venous thromboembolism is controversial due to tightly balanced risks and benefits of indefinite anticoagulation. Risk stratification tools may assist in decision making. Objectives: We sought to determine the relationship between residual pulmonary embolism assessed by baseline ventilation-perfusion scan after completion of 5–7 months of oral anticoagulant therapy and the risk of recurrent venous thromboembolism in patients with the first episode of unprovoked pulmonary embolism. Methods: We conducted a multicentre prospective cohort study of participants with a first, unprovoked venous thromboembolism enrolled after the completion of 5–7 months of oral anticoagulation therapy. The participants completed a mean 18-month follow-up. Participants with pulmonary embolism had baseline ventilation-perfusion scan before discontinuation of oral anticoagulant therapy and the percentage of vascular obstruction on baseline ventilation-perfusion scan was determined. During follow-up after discontinuation of oral anticoagulant therapy, all episodes of suspected recurrent venous thromboembolism were independently adjudicated with reference to baseline imaging. Measurements and main results: During follow-up, 24 of 239 (10.0%) participants with an index event of isolated pulmonary embolism or pulmonary embolism associated with deep vein thrombosis and central assessment of percentage of vascular obstruction on baseline ventilation-perfusion scan had confirmed recurrent venous thromboembolism. As compared to participants with no residual pulmonary embolism on baseline ventilation-perfusion scan, the hazard ratio for recurrent venous thromboembolism was 2.0 (95% CI 0.5–7.3) for participants with percentage of vascular obstruction of 0.1%–4.9%, 2.1 (95% CI 0.5–7.8) for participants with percentage vascular obstruction of 5.0%–9.9% and 5.3 (95% CI 1.8–15.4) for participants with percentage vascular obstruction greater than or equal to 10%. Conclusions: Residual pulmonary embolism assessed by pulmonary vascular obstruction on baseline ventilation-perfusion performed after 5–7 months of oral anticoagulant therapy for the first episode of unprovoked pulmonary embolism was associated with a statistically significant higher risk of subsequent recurrent venous thromboembolism. Percentage of pulmonary vascular obstruction assessment by ventilation-perfusion scans maybe a useful tool to help guide the duration of oral anticoagulant therapy after a first unprovoked pulmonary embolism. Trial registration: Registered atwww.clinicaltrials.gov identifier:NCT00261014 . Highlights: Optimal duration of OAT after a first, unprovoked VTE is controversial. Better prediction of the risk of recurrent VTE after OAT discontinuation is necessary. Residual PE can be assessed by percentage of vascular obstruction (PVO). PVO after 5–7 months OAT was associated with a higher risk of recurrent VTE. PVO assessment by V/Q scans maybe a useful tool to help guide the duration of OAT.